The Value of Antenatal Ultrasound in Diagnosing Anatomical and Morphological Abnormalities of the Fetal Umbilical Vein - Chunguo Zhang; Jing Zhao; Hongli Wang; Xiaoxia Zha; Lihong He (IMR Press, 2023)
Background: Normally, fetal umbilical vein (UV) starts from the capillary network in the chorionic villus and accompanies the umbilical artery (UA). After leaving the placenta, it courses along within the umbilical cord. As the embryo develops, the proximal segment of both the right and left umbilical veins obliterate, and the distal end of the left umbilical vein enters the liver. The microvessels passing through the liver gradually merge and communicate with the hepatic sinus to form the ductus venosus, which then drains into the inferior vena cava (IVC). UV anatomical and morphological abnormalities in complex and variable forms often lead to poor fetal prognosis. In light of this, a thorough prenatal ultrasound providing detailed information on UV abnormalities is potentially clinically significant. Methods: The sonographic features and clinical data of fetuses diagnosed with abnormal umbilical vein anatomy and morphology by antenatal ultrasonography from January 2016 to December 2021 in Sichuan Provincial Maternity and Child Health Care Hospital were retrospectively analyzed. Results: A total of 403 fetuses were included in the study. Among them, 318 cases were diagnosed with intrahepatic persistent right umbilical vein, and 44 cases experienced intracardiac malformations, 34 cases with extracardiac malformations, and 14 cases with both intra- and extracardiac malformations. Three cases had double umbilical veins; 1 case with intracardiac malformation and 1 case with extracardiac malformation. Eighty cases were diagnosed with umbilical vein varix (manifested as intra- or extra-abdominal vein varix or umbilical vein aneurysm); 2 cases with intracardiac malformations and 11 cases with extracardiac malformations. Two cases were diagnosed with umbilical vein stenosis, with neither of them combined with other malformations. Among the 403 fetuses, 86 received genetic testing with 8 of them confirmed with chromosomal abnormalities and the remaining 78 being normal. Of the 8 cases, 7 were diagnosed with persistent right umbilical vein (PRUV) and 1 had umbilical vein stenosis. As related to pregnancy outcomes, 386 fetuses had no obvious abnormalities being observed during the subsequent 2 years' follow-up and 17 cases were terminated due to serious malformations. Conclusions: Antenatal ultrasound assists in the accurate diagnosis of anatomical and morphological abnormalities of the umbilical vein. For cases with no other malformations or chromosomal abnormalities, a better prognosis can be expected and careful follow-up is required, whereas for those with severe malformations or chromosomal abnormalities, the prognosis is often poor. Prenatal ultrasound should provide careful examination to determine whether the fetal umbilical vein has normal anatomy and morphology, thereby supporting better prenatal outcomes.